Frenemy in Media: Maritime Sovereignty and Propaganda on South China Sea - Lupita Wijaya (Center for Southeast Asian Social Studies (CESASS), 2018)
When Indonesia struggles to fight illegal fishing in 2016, Indonesian Navy has caught several Chinese fishing boats in its 200-mile exclusive economic zone (EEZ) off the Natuna Island. Although, many have trespassed Indonesia’s EEZ, conducted illegal fishing and been scuttled, China is the only country that backs up their fishermen with military forces. After Indonesia officially sent diplomatic protest note over the incident, China replied that the seizing had no official grounded as the area was actually claimed as traditional fishing ground by China. This position may leave Indonesia in frenemy position with China. Regional conflict such as South China Sea has been diligently highlighted in international coverage. If it’s about involvement of home country conflict, the concept of objectivity journalism has been under questioned. This embodied-concept has raised because of broad range of contextualization in international coverage. Interdependency between media systems and political systems interprets how propaganda influences on the media within the national interest frames of ideology, particularly when the global issue involving their home countries. There are nine propaganda techniques including name calling, glittering generalities, transfer, testimonial, plain folks, card stacking, bandwagon, frustration of scapegoat and fear. Applying comparative content analysis of Indonesian and Chinese state-run wire services of ANTARA and Xinhua, and three most popular news websites: China Daily, People’s Daily and Kompas this study identifies types of national interest frames including common, conflict, and threat interest frames. It is found out that media perform propaganda techniques which later depict the frenemy position according to their national interest frames.